ANALISA MASALAH DAN STRATEGI PENGELOLAAN SAMPAH RUMAH TANGGA DAN SAMPAH SEJENIS RUMAH TANGGA DI KABUPATEN BLITAR - Syah Alam Agungdiningrat; M. Abdus Salam Jawwad (Nusantara Hasana Journal, 2023)
Population growth and progress in the level of the economy in Blitar Regency directly affect the increase in the amount of waste. If this waste is not managed properly, it will affect the level of cleanliness and reduce aesthetics and pollute the environment, which in turn will reduce the level of public health. This study aims to provide strategic recommendations for household and household similar waste management systems in Blitar Regency so that waste reduction and handling becomes more effective and efficient. This study used the guidelines of SNI 3242:2008 for waste management in settlements, SNI 19-2454-2002 concerning operational technical procedures for managing municipal solid waste, and Regulation of the Minister of Public Works of the Republic of Indonesia Number 03/PRT/M/2013 concerning the implementation of waste management infrastructure and facilities in Handling of household waste and household-like waste. The strategy for the need for waste management facilities and infrastructure at the village/kelurahan level in Blitar Regency includes containers at waste sources where residents and public facilities are increased by adding units and capacity, adding garbage collection devices that can reach narrow alleys or densely populated areas and trucks to move them from TPS to landfill.